Comments on EuroFlow standard operating procedures for instrument setup and compensation for BD FACS Canto II, Navios and BD FACS Lyric instruments - Glier, Hana; Novakova, Michaela; Te Marvelde, Jeroen; Bijkerk, Andre; Morf, Daniela; Thurner, Daniel; Rejlova, Katerina; Lange, Sandra; Finke, Judith; van der Sluijs-Gelling, Alita; Sedek, Lukasz; Flores-Montero, Juan; et al. (Journal of immunological methods, 2019)
This commentary discusses particularities of application of the EuroFlow standardization of flow cytometric analyses on three different flow cytometers. The EuroFlow consortium developed a fully standardized approach for flow cytometric immunophenotyping of hematological malignancies and primary immunodeficiencies. Standardized instrument setup is an essential part of EuroFlow standardization. Initially, the EuroFlow Consortium developed and optimized a step-by-step standard operating procedure (SOP) to setup 8-color BD FACSCanto II flow cytometer (Canto), with the later inclusion of Navios (Beckman Coulter) and BD FACSLyric (Lyric). Those SOPs were developed to enable standardized and fully comparable fluorescence measurements in the three flow cytometers. In Canto and Navios, mean fluorescence intensity (MFI) of a reference peak of Rainbow beads calibration particles is used to set up photomultiplier (PMT) voltages for each detector channel in individual instruments to reach the same MFI across distinct instruments. In turn, a new feature of Lyric instruments allows to share collection of attributes that are used to place the positive population at the same position among instruments in the form of assays, as one of its components integrated in the Cytometer Setup and Tracking (CS&T) module. The EuroFlow Lyric assays thus allow for standardized acquisition of 8-color EuroFlow panels on Lyric without the need to setup the PMT voltages on the individual instruments manually. In summary, the standardized instrument setup developed by EuroFlow enables cross-platform inter- and intra-laboratory standardization of flow cytometric measurements. This commentary provides a perspective on the modifications of the standardized EuroFlow instrument setup of Canto, Navios and Lyric instruments that are described in detail in individual instrument-specfic SOPs available at the EuroFlow website.
Keywords: Reference Standards; Standardization; Flow cytometry; Navios; průtoková cytometrie; Instrument setup; lidé; BD FACSLyric; EuroFlow; Immunophenotyping; Humans; referenční standardy; imunofenotypizace; Flow Cytometry